THE INFLUENCE OF THE PRINCIPAL’S MANAGERIAL COMPETENCE, WORK CLIMATE AND TEACHER’S SELF CONCEPT - SUMINAR, Suminar (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
The purpose of this study is to analyze, test and find out: the influence of the principal's managerial competence, work climate and teacher's self-concept on the performance of public elementary school teachers in Karawaci District, Tangerang City. The method used in this study is a causal survey method with a path analysis technique. The population in this study is all elementary school teachers in State Elementary School in Karawaci District, Tangerang City, totaling 180 teachers with a sample of 124 teachers taken based on proportional random sampling. The analysis technique used is the path analysis technique. Based on the results of the analysis, it is known: 1) There is a direct positive and significant influence of the principal's managerial on teacher performance; 2) There was a direct positive and significant influence of work climate on teacher performance; 3) There was a direct positive and significant influence of teachers' self-concept on teacher performance; 4) There was a direct positive and significant influence of the principal's managerial on the teacher's self-concept; 5) There was a direct positive and significant influence of work climate on teachers' self-concept; 6) There was a direct positive and significant influence of the principal's managerial on the work climate.